Pre-Christian and Christian Symbols in Ukrainian Folk Art: Sign-Letter System - STELMASHCHUK, Halyna; LEVKOVYCH, Nataliya; MALANCHUK-RYBAK, Oksana; PATYK, Roksolana; TSYMBALA, Lada; HONCHARUK, Oleksandr (The journal of contemporary issues in business and government, 2021)
Symbols for centuries keep their semantic load and are transmitted to descendants; they are placed on interior items, clothing accessories, household items, and many other products. Folk embroiderers include symbols into compositional schemes on rushnyky (Ukrainian traditional towels) and vyshyvanky (Ukrainian traditional shirts). Using comparative, semantic, and semiotic methods, we highlight the semantic meaning of the sign-letter system in Ukrainian folk art and the prospects for its functioning in modern design. The results of the research can be implemented in the modern design of products, focusing on the decorative and semantic meaning of the sign-letter system in the modern environment.